Sublinear functionals ergodicity and finite invariant measures - G. Das; B. K. Patel (International Journal of Mathematics and Mathematical Sciences)
By introducing a sublinear functional involving infinite matrices, we establish its connection with ergodicity and measure preserving transformation. Further, we characterize the existence of a finite invariant measure by means of a condition involving the above sublinear functional.